The Use of Metaverse in Providing Interactive Learning Experiences in Schools - Haryo, Petrus; Makmur, Amelia (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
The development of digital technology has played an increasingly important role in education, and the concept of the metaverse offers the potential to enhance the quality of learning. The implementation of metaverse in education is gradually taking place, but understanding and utilization are still limited, especially at the primary and secondary school levels. This is further reinforced by the fact that Indonesia still adheres to mass education or education 2.0. This statement reflects the limitations in understanding and utilizing the concept of metaverse in school-based learning. This research aims to explore the utilization of metaverse as an interactive learning tool in the school environment. The research method used is a survey method, with educators at the primary and secondary school levels as respondents. Quantitative descriptive analysis is employed to determine the values of the related variables. The results of this research show that 40.4% of the respondents state that integrating social media with the metaverse can enhance the engagement and relevance of learning, creating interesting and interactive learning experiences. The metaverse also supports virtual social interactions, collaborative learning, and strengthens relationships with learners from diverse backgrounds. However, 47.4% of the respondents state that the integration of metaverse in learning practices is still limited, and learners' understanding of the metaverse needs to be improved. Further efforts are needed to integrate the metaverse into learning practices at schools, develop effective learning materials, and address existing challenges. In conclusion, the use of metaverse in learning has the potential to enhance learner engagement, creativity, collaboration, and motivation, but it requires more intensive efforts to fully integrate it into learning practices at schools.